Relationship Between Internal Audit Practices And Performance Of Water Service Providers In Kenya - Ndimitu, Perminus Nyaga; Mwangi, Cyrus Iraya; Kisaka, Sifunjo; Mwangi, Mirie (Archives of Business Research, 2018)
The purpose of this study was to establish the relationship between internal audit and organisational performance of Kenyan WSPs. To fulfil the study objective, hypothesis was derived and tested on a population of 93 Water service providers. This cross sectional descriptive study was guided by a positivist study paradigm. The Data Envelopment Analysis approach was used to codify the dependent variable and regression analysis was then applied to test the hypothesis. The null hypothesis was rejected as the regression analysis found that 10.1% of variations in firm performance are explained by variation in internal audit while 89.9% of variations are explained by other variables. This infers that internal audit influences performance of Water service providers in Kenya. The study made contribution to policy formulation and development to benefit the understanding on how internal audit in the Kenyan context influence organizational performance resulting to formulation of reforms in various public institutions to strengthen internal audit.